2017
DOI: 10.1177/0170840616679454
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Control Systems and Stakeholder Networks in Shaping the Identities of Self-Managed Teams

Abstract: Team identity has received little research attention even though an increasing number of firms are moving \ud to team-based organizations and there is evidence that teams form identities. We explore the extent to \ud which team identity can be institutionalized as a central organizing principle of team-based firms. We argue \ud that managerial and stakeholder interventions shape the self-construction of team identity as well as the \ud team’s commitment to specific work objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 87 publications
0
14
0
1
Order By: Relevance
“…Organizations need to recognize and promote shared leadership parallel to formal or hierarchical leadership. The increase of self-managed teams and agile team collaboration in organizations points to the value of shared leadership in teams, rather than relying only on formal leadership guidance (e.g., Annosi et al, 2017;Solansky, 2008). Such developments toward more shared leadership in teams can be actively supported by formal leaders in an organization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Organizations need to recognize and promote shared leadership parallel to formal or hierarchical leadership. The increase of self-managed teams and agile team collaboration in organizations points to the value of shared leadership in teams, rather than relying only on formal leadership guidance (e.g., Annosi et al, 2017;Solansky, 2008). Such developments toward more shared leadership in teams can be actively supported by formal leaders in an organization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The stakeholders of the HEIs, such as students, employers, employees, alumni, parents, donors and government institutions, require the management to implement sound strategies to safeguard their interests. Previous studies have shown that there is a positive association between the stakeholders and the strategy used (Frooman, 1999;Sharma;Henriques, 2004;Li;, as well as a positive association between the stakeholders and the management control system (Annosi et al, 2017;Barnett et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Finally, we consider team identification as a powerful sense‐making tool that gives direction and motivates the individual within self‐managing teams (Annosi, Foss, Brunetta, & Magnusson, 2017; van Knippenberg & van Schie, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%